2020
DOI: 10.3390/md18090468
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction of Bioactive Peptides from Monkfish (Lophius litulon) and Characterization of Their Role in H2O2-Induced Lesion

Abstract: Background: Marine fish meat has been widely used for the extraction of bioactive peptides. This study was aimed to optimize the preparation of monkfish muscle peptides (LPs) using response surface methodology (RSM) and explore the antioxidant activities of <1 kDa LPs. Methods: Peptides were prepared from the muscles of monkfish (Lophius litulon), and five proteases were tested to hydrolyze muscle proteins. The hydrolysate that was treated using neutrase showed the highest degree of hydrolysis (DH) and 1,1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…The results showed that the antiradical activity of BH against ABTS •+ ranged from 23.09% at 1 mg/mL to 62.07% at 5 mg/mL with IC 50 of 3.81 mg/mL. Concentrationdependent activity in the ABTS assay was consistent with previous results, which found that increased fish protein hydrolysate concentrations resulted in increased antioxidant activity [Chalamaiah et al, 2013;Tian et al, 2020]. Latorres et al [2018] reported that the ability of protein hydrolysate to scavenge the ABTS •+ was associated with the size of the peptide chain and the enzyme specificity to break the peptide bonds during the enzymolysis.…”
Section: Antioxidant Activities Of Bhsupporting
confidence: 89%
“…The results showed that the antiradical activity of BH against ABTS •+ ranged from 23.09% at 1 mg/mL to 62.07% at 5 mg/mL with IC 50 of 3.81 mg/mL. Concentrationdependent activity in the ABTS assay was consistent with previous results, which found that increased fish protein hydrolysate concentrations resulted in increased antioxidant activity [Chalamaiah et al, 2013;Tian et al, 2020]. Latorres et al [2018] reported that the ability of protein hydrolysate to scavenge the ABTS •+ was associated with the size of the peptide chain and the enzyme specificity to break the peptide bonds during the enzymolysis.…”
Section: Antioxidant Activities Of Bhsupporting
confidence: 89%
“…We selected acid protease to hydrolyze monkfish skin based on its efficiency. Unlike in our previously published research, we found neutrase to be the best enzyme for preparing peptides derived from monkfish meat (31). This may be attributed to the disparities in the protein composition.…”
Section: Preparation Of Pscp From the Skin Of Monkfishcontrasting
confidence: 99%
“…We previously found that LPs had a high antioxidant activity and could effectively scavenge DPPH, hydroxyl, ABTS, and superoxide anion radicals, and protect RAW264.7 cells from H 2 O 2 -induced injury. LPs can be used as raw materials for natural antioxidants [ 26 ]. In order to provide a theoretical basis for the stable development and application of LPs and related products, we systematically analyzed the composition of LPs and identified the corresponding proteins using both database search and de novo sequencing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Monkfish meat has traditionally been considered a low-value food. Monkfish peptides (LPs) have been found to have strong antioxidant activities and fat absorption capabilities [ 26 , 27 , 28 ]. However, the regulatory effects of LPs on NAFLD, and the underlying molecular mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%